STRATEGI PENGUATAN KINERJA KARYAWAN MELALUI DISIPLIN DAN MOTIVASI KERJA [STRATEGIES FOR STRENGTHENING EMPLOYEE PERFORMANCE THROUGH WORK DISCIPLINE AND WORK MOTIVATION] - Septiani, Yeni (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to analyze strategies for strengthening employee performance through work discipline and work motivation at PT Makmur Jaya Abadi. The research adopts a quantitative approach using a survey method, with data collected through structured questionnaires distributed to all respondents, totaling 55 employees. Work discipline and work motivation are positioned as strategic factors that contribute to the optimization of employee performance. Data analysis was conducted using inferential statistical techniques to identify the contribution of each variable in shaping employee performance. The findings indicate that the consistent implementation of work discipline, supported by strong work motivation, is able to strengthen employee performance in a sustainable manner. These results suggest that human resource management strategies emphasizing compliance with work regulations and the fulfillment of employees’ motivational needs play a crucial role in enhancing productivity and performance quality. This study provides practical implications for the management of PT Makmur Jaya Abadi in formulating human resource development policies oriented toward effective and sustainable employee performance improvement.